Multiprofessional team action in the face of care for hospitalized children: an integrative review - Carvalho, Richard Morrinson Couras de (2021)
The aim of this study was to investigate the performance of the multiprofessional team; Interpersonal relationships: multiprofessional team and family and the challenges and possibilities of multiprofessional practices. A systematic review of the literature was carried out, based on the search for scientific articles indexed in the databases Pubmed, ScienceDirect, Lilacs and Scielo, using as descriptors: multiprofessional team, hospitalization and child, combined with Boolean operators, as well as their translations for the English and Spanish. After the search, 4,295 scientific productions were found, applying filters and establishing the inclusion and exclusion criteria, the final result was 19 articles that comprised the sample. Based on the findings, the discussion was categorized into themes that involve the performance of multiprofessional practice, such as: Multiprofessional team; Interpersonal relationships: multiprofessional team and family; Challenges and the possibility of multiprofessional practices. The work process of the multidisciplinary team is directly related to the professionals' conception of the meaning of teamwork and the importance in the development and quality of the assistance provided. For success, it is necessary to focus attention on the demands that emerge in the hospital routine, as well as providing the strengthening of team-team bonds, as well as team-family, thus enabling effective communication providing the hospitalized child with comprehensive and assertive care from the association of these practices.